73.7k views
4 votes
Can anybody help me with understanding how to do -2+a/3 = -4?

User Pranathi
by
5.1k points

2 Answers

3 votes
A=-14!!!!!!!!! Hope it helps ...........
User Jackuars
by
6.0k points
5 votes

Answer:

a = -14

Explanation:

a-2/3=-4. Multiply -4 by 3 to get rid of the denominator. This leaves you with a-2 = -12. Move the -2 to the other side to get a = -2-12, which simplifies to a = -14.

User Jubbles
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.